IMPROVING STUDENTS’ LEARNING MOTIVATION BY APPLING GROUP GUIDANCE FOR CLASS VII STUDENTS AT SMP NEGERI 2 SENTAJO RAYA - Iriadi, Wawuk Eka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research was started by the low motivation of students in learning. This research was conducted at SMP Negeri 2 Sentajo Raya with a total of 24 students consisting of 13 male students and 11 female students. This type of research was a classroom action research by applying group guidance. The action research design in this study included planning, action, observation, and reflection. The results showed that students who had very high intervals were only 4 (16.6%) people, after taking action in cycle I increased to 7 (29.2%) people, and in cycle II it increased again to 9 (37.5%) people. The interval of students categorized as high before the action was 6 (25%) people, in cycle I it increased to 9 (37.5%) people and cycle II to 12 (50%) people. The students’ interval in moderate category before the action was 8 (33.4%) people, in the first cycle it decreased to 5 (20.8%) people and in the second cycle it decreased again to 3 (12.5%) people. The interval of students in the low category before the action was 5 (20.8%) people, in cycle I it was reduced to 3 (12.5%) people and in cycle II there were no students in the low category. Students’ interval in the very low category before the actions was 1 (4.2%) people, and in cycles I and II there was none. It can be concluded that student motivation can be improved through group guidance at SMP Negeri 2 Sentajo Raya.